2017
DOI: 10.1002/cam4.1070
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated short‐course radiotherapy in elderly patients with glioblastoma multiforme: an analysis of the National Cancer Database

Abstract: For elderly patients with glioblastoma multiforme (GBM), randomized trials have shown similar survival with hypofractionated short‐course radiotherapy (SCRT) compared to conventionally fractionated long‐course radiotherapy (LCRT). We evaluated the adoption of SCRT along with associated factors and survival in a national patient registry. Using the National Cancer Data Base (NCDB), we identified patients aged ≥70 years with GBM, diagnosed between 1998 and 2011, who received SCRT (34–42 Gy in 2.5–3.4 Gy fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…The results of the current study are consistent with the ndings of other studies in various cancers [25][26][27][28] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of the current study are consistent with the ndings of other studies in various cancers [25][26][27][28] .…”
Section: Discussionsupporting
confidence: 93%
“…A study of glioblastoma patients who received chemoradiation therapy after surgical resection or biopsy reported improved OS for patients treated at academic facility compared to patients treated at community hospitals (HR: 0.86, CI: 0.82-0.91) 27 . Receiving treatment at an academic hospital was associated with improved OS in a study of patients age ≥ 70 diagnosed with glioblastoma (HR: 0.76, CI: 0.66-0.86) compared to receiving treatment at non-academic facilities 26 for patients diagnosed with BMs from NSCLC 23 . In our study, academic centers were more likely to use chemotherapy (56% vs. 53%) and RT (74% vs. 71%) compared to non-academic centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monetary and socioeconomic aspects of oncologic and radiotherapeutic care are easily apparent from these data, which are crucial to consider in the pursuit of equalopportunity care in the United States going forward. Owing to monetary/billing issues, community and private practices are well-documented to offer conventional fractionation for many neoplasms for which there is level I evidence for hypofractionation (15)(16)(17), and herein we demonstrate a similar situation for RC cases. Further proving these points were the findings that patients with private insurance and higher incomes were more likely to receive CFRT, likely related to the "fee-for-service" billing model widely in effect in the United States.…”
Section: Discussionmentioning
confidence: 52%
“…In the literature, the data of the overall survival (OS) among elderly patients who were treated with standard and hypofractionated RT are different. Mak et al found that patients treated with hypofractionation radiotherapy had worse OS than the others with standard course RT [9]. On the other side, Row et al found that there were no difference in OS among the groups [10].…”
Section: Radiation Therapy Of the Brain Tumors In The Era Of Covid-19mentioning
confidence: 99%